Effect of Predisposing Factors (Education, Economic Level, Knowledge and Attitude) on Defecation Behavior in Bener Meriah Regency - Syarifah; Ida Yustina; Namora Lumongga Lubis (Britain International of Exact Sciences (BIoEx) Journal, 2020)
This study discusses about factors affecting predisposing factors (education, economic level, knowledge and attitude) on defecation behavior in Bener Meriah Regency. This research was conducted in Bener Meriah Regency which consists of 10 districts with the following considerations: (1) Indiscriminate defecation (BABS) behavior of 36.7 percent, this is far from the minimum service standard target (SPM) of 100 percent the community does not defecate carelessly; (2) Achievement of clean and healthy living behavior is only 24.7 percent, (3) Achievement of total community-based sanitation is only 3.0 percent of the target of 100 percent; (4) The research location is easy to reach by researchers. The result shows that The education of the head of the family has an influence on the behavior of open defecation. The economic level of the head of the family influences the behavior of open defecation. The attitude of the head of the family has an influence on the behavior of open defecation